Menarik Minat Pemustaka Dengan Melakukan Pemasaran Jasa Informasi Perpustakaan Untuk Generasi Milenial - Pradita Ruskia Amanda (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to develop the library by managing and managing the library in accordance with the National Standards for Higher Education Libraries, to create a good image of the library in the eyes of users, the library needs to determine steps to make the library attractive and attractive to users. This study uses the best practice sharing method where the method of implementing a concept or technology is widely used by individuals and organizations. One way is by marketing library information services. It is important to inform the public, especially young people, that the library does not only focus on conventional services and collection development, but that there is added value that is expected in its development by creating strategies, innovations that can attract the interest of users. In conclusion, we know that the users we face today are the younger generation or millennial generation who are more adept at technological developments.